The systems psychodynamic role identity of academic research - Cilliers, F. (South African Journal of Higher Education, 2017)
Research on the unconscious role behaviour of academic research supervisors is limited. The aim of this research was to study and describe the systems psychodynamic role identity of a group of academic research supervisors. A qualitative in-depth socio-analytic interview was used as the data-gathering instrument. A convenient and purposive sample was drawn consisting of 11 supervisors at a large South African university. Systems psychodynamic role analysis was used as the data analysis method. The findings indicated an experienced difference between the normative, existential and phenomenal roles demonstrating their high levels of anxiety, being introjected and projected onto them. Recommendations for the institution and further research were formulated.